A critical study on wittgenstein's logical analysis on language - Sivakaran, N. (university of Jaffna, 2014)
The objective of this paper is an attempt to explicate the two different kind of logical analysis of Wittgenstein, which was formulated in his two reputed books Tractatus and Philosophical Investigation, in order to elucidate the meanings of sentence by analyzing the basic structure of the language. Wittgenstein attempts to show that all the traditional philosophical problems can be avoided entirely by application of an appropriate logical analysis. The analysis of language is an important tool for solving philosophical problems. The role of language is a central concerned in his philosophy, because Philosophy, in general, is a study of knowledge. Knowledge is conveyed through our ordinary language; in other words, it is ordinary language that carries knowledge. However, the ordinary language often creates troubles in understanding the true meaning of philosophy. It also creates ambiguity and confusion. Therefore, the ambiguity and uncertainties inherent in language misleads understanding of knowledge. Wittgenstein believes that by explicating “language” they could unravel the meaning of knowledge as an objective independent entity. In this way Wittgenstein, as an analytic philosopher, adopted two different analytic methods to analyze language and produced two philosophies on the basis of his theories of meaning which are picture theory and language game. Therefore, this study intends to explicate these two theories of meaning through the Wittgenstein' different analytic method. This study mainly a qualitative research solely based on a literature review on the different method of Wittgenstein and hence scholarly original works of Wittgenstein will be reviewed. As such analytic, descriptive and comparative methods will be employed to reveal Wittgenstein's direction of philosophical activity on language. This study gathers a details reference from the original writings of the Wittgenstein. In addition, secondary related sources such as books, related documents, paper clipping and various other details from the internet will be utilized for this research. Keywords: Analysis, Language, Picture theory, L
Keywords: Analysis; Language; Picture theory; Language game